2006
DOI: 10.1177/1464884906065522
|View full text |Cite
|
Sign up to set email alerts
|

Is changing the language enough? The Spanish-language ‘alternative’ in the USA

Abstract: Alternative voices in the USA have been found in ethnic media outlets that provide information in languages other than English and focus on issues often ignored by the mainstream news. One such example is the Spanish-language media, which have had a long history in the USA. A content analysis was performed to analyze broadcast news in San Diego County to assess the similarities and differences between an ethnic news channel, KBNT (Univisión affiliate), and a mainstream station, KGTV (ABC affiliate). The data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…The digital divide has been remedied to some degree given broader adoption of smartphone use among Blacks and Hispanics in the U.S., although traditional access through a home computer remains inequitably distributed for these same groups when compared to Whites [47]. Maintenance of culture through enjoyment of ethnic media continues [48], suggesting that although a platform may be similar (e.g., the Internet), particular message streams (e.g., specific webpages) or information sources tailored to communities of interest may be more powerful than a general expectation that increased access will facilitate generic messaging approaches across all ethnic/racial groups [48].…”
Section: Introductionmentioning
confidence: 99%
“…The digital divide has been remedied to some degree given broader adoption of smartphone use among Blacks and Hispanics in the U.S., although traditional access through a home computer remains inequitably distributed for these same groups when compared to Whites [47]. Maintenance of culture through enjoyment of ethnic media continues [48], suggesting that although a platform may be similar (e.g., the Internet), particular message streams (e.g., specific webpages) or information sources tailored to communities of interest may be more powerful than a general expectation that increased access will facilitate generic messaging approaches across all ethnic/racial groups [48].…”
Section: Introductionmentioning
confidence: 99%
“…Several scholars -Cormack and Hourigan (2007), Davila (2001), Downing (1992), Henningham (1992), Lewis (2008), Moran (2006), Pietikäinen (2008) and Moring et al…”
Section: Pacific Media In Aotearoa New Zealandmentioning
confidence: 99%
“…She agrees, in line with many other studies (Arnold & Schneider, ; Howley, ; Riggins, ; Viswanath & Arora, ), that ethnic media enhance community building as a balance between majority and minority culture, perform social control through their selective news coverage and advertising, and fulfill an assimilatory and informational function. Other research has examined Asian and Latino immigrant groups’ transnational activities (Lin et al, ), geo‐ethnic storytelling (Lin & Song, ) and ethnic media's role as an alternative to mainstream news channels (Moran, ). Lin et al () also looked the role ethnic newspapers play in enabling a transnational, cross‐border life in both global and local dimensions.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the case of Hispanic immigrant journalists, influences on content from within newsrooms or at the individual level have been the subject of much study, with a focus on Spanish‐language mainstream news; in these instances, researchers have often found more similarities than differences with English‐language counterparts. For example, Subervi's () look at the educational and professional formation of those working within mainstream Spanish‐language media in the United States found that approximately 50% of journalists studied in traditional journalism programs in American universities together with their English‐language counterparts, a finding that might also account for similarities in news values (Moran, ). Given these findings, and previous research on connections between journalistic practices and the functioning of a public sphere, questions about the ways in which topics are reported for immigrant audiences by immigrant outlets are important for understanding the potential democratic functions of these outlets in transnational context.…”
Section: Theoretical Frameworkmentioning
confidence: 99%